Analysis of Factors Affecting Financial Performance in Foods and Beverage Companies Listed in Indonesia Stock Exchange 2018-2020 Period - Ricky Rafii Ritonga; Nadia Gloria Bangun; Chavia Zagita; Yenny (Publisher Cv. Inara, 2022)
His study has a goal, namely to examine the effect of the Current Ratio, Debt to Equity Ratio, Net Profit Margin, and Return On Equity on the Financial Performance of a manufacturing company listed on the Indonesia Stock Exchange. This study was carried out using a Quantitative Research approach. The research category is Descriptive Research. The population of this research is 75 Manufacturing Companies listed on the Indonesia Stock Exchange 2018-2020. The sampling technique used was the purposive sampling technique and 45 sample companies were obtained within 3 years. Related variables in this study are Liquidity (Current Ratio), Solvency (Debt to Equity Ratio), Profitability (Net Profit Margin), Profitability (Return On Equity), and Financial Performance (Return On Assets). The results of this study prove that the partial (t-test): CR, DER, NPM, and ROE have no significant effect on financial performance (ROA). Simultaneously (f test), the probability scale (Sig.) is 0.000 < 0.05, and the results from Fount 401.450 > 2.60 are Ftable results. Then the result of the calculation is 2.60. And the results of statistical testing can be concluded that the Independent Variables: Current Ratio, Debt to Equity Ratio, Net Profit Margin, and Return On Equity have a significant influence on financial performance (Return On Assets).